IVABRADINE HYDROCHLORIDE DIRECTLY COMPRESSED TABLETS USING NANO-CELLULOSE EXTRACTED FROM ARACHIS HYPOGAEA SHELLS - JEEVANA JYOTHI B; APARNA J (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of this work was the extraction of nanocellulose from Arachis hypogaea shells, characterization of nanocellulose, development, and in vitro evaluation of directly compressed tablets of ivabradine hydrochloride (IVH) using nanocellulose. Methods: IVH and colloidal silicon dioxide are gift samples from Mylan Laboratory, Hyderabad, and Karnataka Antibiotics and Pharmaceuticals Ltd., Bengaluru, respectively. Nanocellulose was extracted from A. hypogaea shells by alkaline treatment followed by acid hydrolysis and it was characterized by particle size analysis by zeta sizer, melting point determination, differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) analysis. Compatibility between IVH and nanocellulose was confirmed by FTIR and DSC analysis. Then, fast-release tablets of containing 5 mg of IVH were prepared by direct compression using various compositions containing nanocellulose, starch, and colloidal silicon dioxide and evaluated. Results: Nanocellulose in the size of 273.4 nm was extracted from A. hypogaea shells to possess its ideal characteristics. IVH and nanocellulose were compatible according to FTIR and DSC analysis. Fast-release tablets of IVH were prepared as directly compressed tablets by direct compression. Tablets made with 5 mg of IVH and nanocellulose, starch, and colloidal silicon dioxide evidenced fast release of 96.37% in 5 min. Conclusion: Nanocellulose from A. hypogaea shells can be produced successfully by alkali treatment followed by acid hydrolysis, ball milling, and lyophilization. This nanocellulose can be exploited successfully for the design of fast-release tablets of IVH.